2013
DOI: 10.4067/s0718-16202013000100016
|View full text |Cite
|
Sign up to set email alerts
|

Diet of guanaco in sheep-free rangeland in Tierra del Fuego, Chile

Abstract: A.E. Muñoz, and J.A. Simonetti. 2013. Diet of guanaco in sheep-free rangeland in Tierra del Fuego, Chile. Cien. Inv. Agr. 40(1):185-191. Guanaco (Lama guanicoe), the only native ungulate of Tierra del Fuego, uses the forests more extensively after the introduction of sheep. It is presumed that the regeneration of lenga (Nothofagus pumilio) is hampered by guanaco browsing. In this context, the diet of guanaco in Tierra del Fuego was evaluated through a microhistological analysis of feces in a livestock-free are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
3
8
1
Order By: Relevance
“…On the other hand, although the availability of herbs was relatively high related to the total available biomass inside the forest (and much higher if we consider the adjacent vegas), they were rejected by the guanacos, coinciding with the results presented by other studies (Soler Esteban et al, 2011;Muñoz & Simonetti, 2013). Grasses, instead, although rejected during spring, they were slightly selected during the summer and consumed according to their availability.…”
Section: Guanaco Selectivity Of Forest Understory Speciessupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, although the availability of herbs was relatively high related to the total available biomass inside the forest (and much higher if we consider the adjacent vegas), they were rejected by the guanacos, coinciding with the results presented by other studies (Soler Esteban et al, 2011;Muñoz & Simonetti, 2013). Grasses, instead, although rejected during spring, they were slightly selected during the summer and consumed according to their availability.…”
Section: Guanaco Selectivity Of Forest Understory Speciessupporting
confidence: 72%
“…) Oerst.] and several other low abundant shrubs, seems to constitute an important part of its diet all year round (Raedeke, 1980;Bonino & Pelliza Sbriller, 1991;Soler Esteban et al, 2011;Muñoz & Simonetti, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This foraging behavior could be explained by: 1) J. frigida dominance in slopes (Osorio et al 2011); 2) large areas covered by zonal vegetation (Osorio et al 2011), which can be used by camelids due to its wide home range (Vicuña: 22,1 to 43,5 km 2 , González et al 2013; Guanaco: 65 to 163 km 2 , Contreras et al 2006); and 3), the presence of domesticated animals, which have a negative effect on resource used by wild camelids (Borgnia et al 2008;Muñoz & Simonetti 2013). It is worth mentioning that 299 domesticated animals were registered in the study area (wetlands) (Goats: 267; horses: 32, unpublished data).…”
Section: Botanical Composition Of the Dietmentioning
confidence: 99%
“…This agrees with what was before described about the guanaco diet in Tierra del Fuego, 8,16,19,29,31,32 in arid and semiarid areas of the Patagonia. [34][35][36][37][38] Table 2 Comparison of the vegetal composition of the three studied communities, using the Sörensen Index. Ranch "Estancia Buenos Aires" (EaBA), Ranch "Estancia San José "(EaSJ) and Ranch "Estancia Ushuaia" (EaUs)…”
Section: Resultsmentioning
confidence: 99%
“…The guanaco, as a generalist herbivore of intermediate selection, is capable of consuming most available species of plants, from grasses to ligneous species, but mainly bushes. 14,36,43,44 Indirect evidence suggests that prairies are the preferred habitat for guanacos in Tierra del Fuego, but that they use forest patches due to displacement by sheep. 3 In a continental site where the guanacos were sedentary, it was shown that the ewes excluded guanacos from the prairies through resource competition.…”
Section: Eaba Easjmentioning
confidence: 99%